Ten years of Descemet membrane endothelial keratoplasty: Identifying risk factors and early failure signs - Nicole Mechleb; Maria Rizk; Guillaume Debellemanière; Damien Gatinel; Alain Saad (Indian Journal of Ophthalmology, 2025)
Purpose: To evaluate the effect of surgical indications and complexity on long-term clinical outcomes in Descemet membrane endothelial keratoplasty (DMEK) and identify early signs of graft failure. Design: Retrospective case series of 105 patients who underwent DMEK from March 2012 to December 2014. Methods: Surgical results were analyzed at 1 year, 3 years, 5 years, and 10 years based on surgical indication: fuchs endothelial dystrophy (FECD) (n = 47) and bullous keratopathy (BK) (n = 58), and on the presence of anterior segment comorbidities: simple (n = 63) versus complex (n = 42) DMEK. Results: Fifty-two patients (54 eyes) were followed up for 3 years, 35 patients (42 eyes) reached the 5-year follow-up, and 20 patients (26 eyes) achieved the 10-year follow-up. Simple DMEK procedures and FECD demonstrated significantly better best corrected visual acuity (BCVA) compared to complex DMEK and BK at 1 year, 3 years, 5 years, and 10 years, respectively (P < 0.01). No statistically significant difference in endothelial cell density (ECD) decline was noted between simple and complex DMEK procedures, nor between FECD and BK (P > 0.05). Central and peripheral pachymetry were significantly higher in BK and complex surgeries at 10 years. Conclusion: While DMEK represents a promising therapeutic avenue for corneal decompensation alongside anterior segment comorbidities, extended follow-up indicates a rise in central and peripheral pachymetry in comparison with simple DMEK. This increase could serve as an early indicators of corneal decompensation, potentially leading to reduced survival rates.